Enhanced ε-Poly-L-Lysine Production by the Synergistic Effect of ε-Poly-L-Lysine Synthetase Overexpression and Citrate in Streptomyces albulus - Wang, Aixia; Tian, Wenzhe; Cheng, Lei; Xu, Youqiang; Wang, Xiuwen; Qin, Jiayang; Yu, Bo (Frontiers in Bioengineering and Biotechnology, 2020)
ε-Poly-L-lysine (ε-PL) is a natural amino acid polymer produced by microbial fermentation. It has been mainly used as a preservative in food and cosmetics industries, as a drug carrier in medicines, and as a gene carrier in gene therapy. ε-PL synthase is the key enzyme responsible for the polymerization of L-lysine to form ε-PL. In this study, the ε-PL synthase gene was overexpressed in Streptomyces albulus CICC 11022 by using the kasOp* promoter and the ribosome binding site from the capsid protein of phage φC31, which resulted in a genetically engineered strain Q-PL2. The titer of ε-PL produced by Q-PL2 were 88.2% ± 8.3% higher than that by the wild strain in shake flask fermentation. With the synergistic effect of 2 g/L sodium citrate, the titers of ε-PL produced by Q-PL2 were 211.2% ± 17.4% higher than that by the wild strain. In fed-batch fermentations, 20.1 ± 1.3 g/L of ε-PL was produced by S. albulus Q-PL2 in 72 h with a productivity of 6.7 ± 0.4 g/L/day, which was 3.2 ± 0.3-fold of that produced by the wild strain. These results indicate that ε-PL synthase is one of the rate-limiting enzymes in ε-PL synthesis pathway and lay a foundation for further improving the ε-PL production ability of S. albulus by metabolic engineering.